2022
DOI: 10.1177/15330338221121092
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inhalation Anesthetics on Tumor Metastasis

Abstract: Many factors affect the prognosis of patients undergoing tumor surgery, and anesthesia is one of the potential influencing factors. In general anesthesia, inhalation anesthesia is widely used in the clinic because of its strong curative effect and high controllability. However, the effect of inhalation anesthetics on the tumor is still controversial. More and more research has proved that inhalation anesthetics can intervene in local recurrence and distant metastasis of tumor by acting on tumor biological beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 174 publications
2
4
0
Order By: Relevance
“…Our results indicated that the patients’ immune function was suppressed after anesthesia and surgery in all 4 groups, and PD alleviated the decrease in CD3 + , CD4 + , and dendritic cell counts and CD4 + /CD8 + ratios, and reduced the concentrations of norepinephrine and cortisol in patients undergoing flap reconstruction for oral cancer. These findings are consistent with those of previous studies [3,15–17] which demonstrated that sevoflurane could directly inhibit natural killer cells and induce apoptosis of T lymphocytes, negatively affecting the immune system. [15,16] Propofol has been shown to have protective effects on immunity and direct anticancer effects.…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicated that the patients’ immune function was suppressed after anesthesia and surgery in all 4 groups, and PD alleviated the decrease in CD3 + , CD4 + , and dendritic cell counts and CD4 + /CD8 + ratios, and reduced the concentrations of norepinephrine and cortisol in patients undergoing flap reconstruction for oral cancer. These findings are consistent with those of previous studies [3,15–17] which demonstrated that sevoflurane could directly inhibit natural killer cells and induce apoptosis of T lymphocytes, negatively affecting the immune system. [15,16] Propofol has been shown to have protective effects on immunity and direct anticancer effects.…”
Section: Discussionsupporting
confidence: 93%
“…Reducing cancer cell proliferation and inducing their apoptosis are key strategies to prevent tumor growth. Recent studies have shown that anesthetics not only play a role in analgesia and sedation but can also inhibit drug resistance of tumor cells and inhibit tumor progression ( Ishikawa et al, 2021 ; Jing et al, 2022 ; Saha et al, 2022 ). To obtain a safe and effective anesthetic intervention, we need to understand the mechanism of these anesthetics to prevent cancer recurrence and promote longer postoperative survival.…”
Section: Regulatory Function Of Anesthetics In Cancermentioning
confidence: 99%
“…However, the vast majority of anesthetics (including different types) have been reported to have potential anti-tumor effects. Moreover, the anti-tumor effects of various anesthetics vary depending on the tumor cell line, tumor location, concentration, and substance properties ( Liu et al, 2020 ; Alam et al, 2021 ; Jing et al, 2022 ; Bogár, 2023 ).…”
Section: Regulatory Function Of Anesthetics In Cancermentioning
confidence: 99%
“…However, additional investigations have corroborated that isoflurane does not influence the expression of genes linked to essential features of cancer. As a result, isoflurane has an inhibiting effect on tumor angiogenesis necessitates validation across diverse tumor types [7].…”
Section: Inhalation and General Anestheticsmentioning
confidence: 99%